The Use of Scaffolding Strategy in Teaching English as a Foreign Language in Sri Lanka - Sameem, MAM (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2013)
The English language is a necessity not only for education but also for current culture's admittance to wealth and social prosperity. The English language helps people improve and enhance their social and economic standing, as well as form a dynamic culture and a strong state. It serves a social purpose and makes a vital contribution to societies. The importance of English language is well understood by all the people and English language plays many important roles in Sri Lanka. The purpose of this study, which was done within a sociocultural framework, was to see how scaffolding affected EFL (English as a Foreign Language) students' learning the target language. The research design was mixed method approach: structured interview, observation and questionnaire. The findings of the study show that most teachers in EFL classes are unaware of the scaffolding tactics to test rather than scaffold their students' knowledge. They are required to know how to be motivated, and how important they are developing English language learning students’ skills in mainstream classrooms. The study's findings demonstrated that in the context of teaching English in Sri Lanka, using scaffolding techniques and implementing personalized instructions enhances teaching quality, comprehend learners' awareness, and interactivity.